Chemical Weathering Intensity and Terrigenous Flux in South China during the Last 90,000 Years—Evidence from Magnetic Signals in Marine Sediments - Yang, Xiaoqiang; Peng, Xuechao; Qiang, Xiaoke; Li, Niu; Zhou, Qixian; Wang, Yuejun (Frontiers in Earth Science, 2016)
The level of chemical weathering is strongly affected by climate. We presented magnetic properties associated with element ratios from the northern part of the South China Sea to denote links between chemical weathering intensity and monsoon changes in the previous 90,000 years. The magnetic parameter IRMAF80mT/SIRM, representing the variations of high coercivity minerals in marine sediments accompanied with the Al2O3/TiO2 and the Chemical Index of Alteration (CIA), demonstrates strong chemical and physical weathering processes during the last 84-40 kyr when intensified Asian monsoon and warm climate occurred. High susceptibility, TiO2 content, and relatively coarser magnetic mineral grain (relatively low ARM/SIRM ratio) also suggest more terrigenous clastic flux resulting from intensified physical erosion and river transport ability. During the 40-15 kyr period, a low IRMAF80mT/SIRM as well as chemical proxies indicate weak weathering as the climate cooled and precipitation decreased.